PENINGKATAN PEMAHAMAN KONSEPTUAL MATEMATIKA GURU SEKOLAH DASAR DI WILAYAH 3T RUPAT UTARA - Suhandri; Ramon Muhandaz; Miftahir Rizqa (LPPM Universitas Abdurrab, 2026)
This community service program aimed to improve the conceptual understanding of mathematics among 24 elementary school teachers in the 3T region of North Rupat, where mathematics instruction still tends to be procedural and insufficiently contextual. The program focused on strengthening teachers’ pedagogical and professional competencies through training in conceptual learning and the Realistic Mathematics Education (RME) approach. The community service activity employed Participatory Action Research (PAR), actively involving teachers in the stages of planning, action, observation, and reflection. The implementation included needs identification, pre-assessment, conceptual and RME-based training, and evaluation of program outcomes. Data were collected through teachers’ understanding questionnaires administered before and after the training and documentation, then analyzed using descriptive quantitative techniques, including mean scores, score differences, percentage improvement, and N-Gain, as well as difference testing using the Wilcoxon Signed-Rank test. The results showed an improvement in teachers’ understanding, with the average score increasing from 38.88 to 45.58, equivalent to a 13.42% increase, and an N-Gain score of 0.54, categorized as moderate. The Wilcoxon Signed-Rank test also revealed a significant difference between pre-training and post-training scores (Z=−3.758;p<0.001). These findings indicate that the training program was effective in enhancing teachers’ capacities and has the potential to be replicated in other 3T regions.